Influence of Body Mass Index and Albumin on Perioperative Morbidity and Clinical Outcomes in Resected Pancreatic Adenocarcinoma. - Andrew Hendifar; Arsen Osipov; Jasleen Khanuja; Nicholas Nissen; Jason Naziri; Wensha Yang; Quanlin Li; Richard Tuli (PLoS ONE, 2016)
Obesity is a known risk factor for PDA and recent reports suggest obesity has a negative impact on clinical outcomes in patients with PDA. Pretreatment body mass index (BMI) and serum albumin (SA) have been shown to be associated with worse overall survival in patients with advanced and metastatic PDA. However, minimal data exists on the impact of BMI and SA on perioperative and long-term clinical outcomes in patients with early-stage resected PDA. Herein, we report on the impact of these variables on perioperative clinical outcomes, overall survival (OS) and disease free survival (DFS) in patients with resected PDA. With IRB approval, we evaluated 1,545 patients with PDA treated at a single institution from 2007-2013 and identified 106 patients who underwent upfront resection with curative intent. BMI and SA were calculated preoperatively and at the time of last clinical evaluation. Influence of preoperative BMI, SA, change in either variable, and influence of other clinical and pathologic variables on perioperative morbidity and mortality was assessed. The impact of these variables on DFS and OS was assessed with cox regression modeling and ANOVA. Actuarial estimates for DFS and OS were calculated using Kaplan-Meier methods. Median follow up time was 16 months (3-89). Mean age was 68 years. Median survival was 14 months (3-65) and median time to recurrence was 11 months (1-79). Length of hospital stay was associated with BMI (p = .023), change in BMI (p = .003) and SA (p = .004). Post-operative transfusion rate was associated with SA (p = .021). There was a strong correlation between BMI change and positive margin (p = .04) and lymph node status (p = .01). On multivariate analysis, change in SA (p = .03) and node positivity (p = .008) were associated with decreased DFS. Additionally, preoperative SA (p = .023), node positivity (p = .026) and poor differentiation (p = .045) were associated with worse OS on multivariate analysis. Low preoperative SA was associated with worse DFS and OS in patients with resected PDA. Lower BMI and SA were associated with longer post-operative hospital stay. Our study is one of the first to describe how pre-operative BMI and SA and post-operative changes in these variables impact clinical and perioperative outcomes. This data supports nutritional status and weight loss as predictors of outcome in resected pancreatic cancer patients and warrants further prospective investigation.